Evaluation of bone healing following horizontal distraction osteogenesis in the maxilla and mandible - حدَاد إبراهيم; علي خليل (Latakia University Journal -Medical Sciences Series, 2023)
Objectives: The goal of this study was to evaluate the efficiency of distraction osteogenesis (DO) using expansion screws for treatment of atrophic and deficient jaw bone. Material and Methods: A total of 9 patients (7 men and 2 women; Age 20-36 years) who came with atrophy of alveolar bone were treated by horizontal distraction osteogenesis. The used device consisted of 2 parts: one was an orthodontic expander and the other was a screw-ring The expansion screws were set on the transport bone which was osteotomized as bone splitting method and fixed to the segment using microscrews. The skeletal and soft tissues changes was gauged using radiographs (cbct) and photographs. The overage of follow- up was 4 months. Results: The dehiscence happened in one patient and simple gingival recession of the teeth inside segmental transport in 2 patients The average of bone density in distraction gap after 4 months of the distraction osteogenesis was 497.9. The average of bone density of the the bone defect region after 4 months of the distraction osteogenesis was 554.7 Conclusion: Under the limitations of this study it can be concluded that the distraction osteogenesis using expansion screws leads to the formation of bone tissue with good density and minimal complication.